2014
DOI: 10.1002/ana.24015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of atypical language activation patterns in focal epilepsy

Abstract: Objective Functional magnetic resonance imaging is sensitive to the variation in language network patterns. Large populations are needed to rigorously assess atypical patterns, which, even in neurological populations, are a minority. Methods We studied 220 patients with focal epilepsy and 118 healthy volunteers who performed an auditory description decision task. We compared a data-driven hierarchical clustering approach to the commonly used a priori laterality index (LI) threshold (LI < 0.20 as atypical) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
177
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(198 citation statements)
references
References 59 publications
17
177
2
Order By: Relevance
“…DeSalvo et al language networks, which has been previously observed (16). Although language networks of patients with atypical language dominance included more brain regions, their classification by using this method was robust, at 100% (four of four), assuming that the patient with discordant classification had typical language laterality.…”
Section: Technical Developments: Resting-state Functional Mr Imaging mentioning
confidence: 77%
“…DeSalvo et al language networks, which has been previously observed (16). Although language networks of patients with atypical language dominance included more brain regions, their classification by using this method was robust, at 100% (four of four), assuming that the patient with discordant classification had typical language laterality.…”
Section: Technical Developments: Resting-state Functional Mr Imaging mentioning
confidence: 77%
“…Different patterns of language organization are described in the literature (Goldmann and Golby, 2005;Dijkstra and Ferrier, 2013;Berl et al, 2014). Here, we consider (see Figure 3) three atypical patterns of hemispheric lateralization.…”
Section: Patterns Of Language Reorganizationmentioning
confidence: 94%
“…Neuroimaging methods have provided more precise function-to-structure mapping (Price, 2012) and suggested that language operations are supported by a large, flexible cerebral network (i.e., including areas located outside the classical language regions) distributed within and across hemispheres (Vigneau et al, 2011;Price, 2012). Moreover, the concept of hemispheric dominance has also evolved from dichotomized (left vs. right) processing toward the idea that continuous participation of both hemispheres is the norm (Jung-Beeman, 2005;Berl et al, 2014). According to this idea, the hemispheres interact continuously (Banich, 1995;Gazzaniga, 2000;Bloom and Hynd, 2005;van der Knaap and van der Ham, 2011;Perrone-Bertolotti et al, 2013a,b).…”
Section: General Considerationsmentioning
confidence: 99%
See 2 more Smart Citations